2022
DOI: 10.1177/21650799221135591
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the Bedside Nurse: Grip Strength and Orthopedic Problems Among Nurses and Nursing Students

Abstract: Background: Bedside nurses and nursing students are at increased risk of musculoskeletal injury due to the physicality and complexity of their work. The purpose of this study was to explore the relationship between grip strength and orthopedic injuries or pain among nurses and nursing students. Methods: A cross-sectional study of nursing staff and nursing students at a health sciences university was conducted. The survey consisted of work-related demographics, exercise habits, and validated scales. The Nordic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The signi cantly higher rates of MSK complaints in both upper and lower body among staff nurses highlight the physical demands and potential occupational hazards associated with nursing work(6). These ndings underscore the need for targeted ergonomic interventions and preventive strategies to reduce the risk of MSK disorders in nursing professionals (32). However, the exercise habits, duration, and intensity were found to be similar between the two groups in our sample.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…The signi cantly higher rates of MSK complaints in both upper and lower body among staff nurses highlight the physical demands and potential occupational hazards associated with nursing work(6). These ndings underscore the need for targeted ergonomic interventions and preventive strategies to reduce the risk of MSK disorders in nursing professionals (32). However, the exercise habits, duration, and intensity were found to be similar between the two groups in our sample.…”
Section: Discussionmentioning
confidence: 45%
“…Scores of perceived stress and number of reported MSK problems were negatively associated with grip strength in our study. Similarly, a cross-sectional study found that participants with grip strength at or above the national average had signi cantly lower odds of self-reported orthopaedic problems, indicating a 135% reduced likelihood of experiencing orthopaedic issues compared to those with grip strength below the national average (32).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations